Beginning Ruby 2nd Edition - Cooper, Peter (Apress, 2012)
Ruby is a fun toy. It’s also a serious programming language. Ruby is the jolly uncle who puts in solid 12-hour days at the construction site during the week but keeps the kids entertained come rain or shine. To hundreds of thousands of programmers, Ruby has become a good friend and a trusted servant, and has revealed a new way of thinking about programming and software development. It’s fun and it works. Like the guitar, it’s claimed that Ruby is an easy language to learn and a hard one to master. I’d agree, with some provisions. If you don’t know any programming languages already, Ruby will be surprisingly easy to learn. If you already know some languages such as PHP, Perl, BASIC, C, or Pascal, some of the concepts in Ruby will already be familiar to you, but the different perspective Ruby takes could throw you at first. Like the differences between spoken languages, Ruby differs from most other programming languages not only by syntax, but by culture, grammar, and customs. In fact, Ruby has more in common with more esoteric languages like LISP and Smalltalk than with better-known languages such as PHP and C++.